Ubiquitin control of S phase: a new role for the ubiquitin conjugating enzyme, UbcH7. - Whitcomb, Elizabeth A.; Taylor, Allen. (2016)
Abstract: Events within and transitions between the phases of the eukaryotic cell cycle are tightly controlled by transcriptional and post-translational processes. Prominent among them is a profound role for the ubiquitin proteasome proteolytic pathway. The timely degradation of proteins balances the increases in gene products dictated by changes in transcription. Of the dozens of ubiquitin conjugating enzymes, or E2s, functions in control of the cell cycle have been defined for only UbcH10 and Ubc3/Cdc34. Each of these E2s works primarily with one ubiquitin ligase or E3. Here we show that another E2, UbcH7 is a regulator of S phase of the cell cycle. Over-expression of UbcH7 delays entry into S phase whereas depletion of UbcH7 increases the length of S phase and decreases cell proliferation. Additionally, the level of the checkpoint kinase Chk1 increases upon UbcH7 depletion while the level of phosphorylated PTEN decreases. Taken together, these data indicate that the length of S phase is controlled in part by UbcH7 through a PTEN/Akt/Chk1 pathway. Potential mechanisms by which UbcH7 controls Chk1 levels both directly and indirectly, as well as the length of S phase are discussed and additional functions for UbcH7 are reviewed.; Springer Open.